2002
DOI: 10.1038/nn899
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth cone guidance mediated by G protein–coupled receptors

Abstract: Growing axons navigate by responding to chemical guidance cues. Here we report that growth cones of rat cerebellar axons in culture turned away from a gradient of SDF-1, a chemokine that attracts migrating leukocytes and cerebellar granule cells via a G protein-coupled receptor (GPCR). Similarly, Xenopus spinal growth cones turned away from a gradient of baclofen, an agonist of the GABA(B) receptor. This response was mediated by G(i) and subsequent activation of phospholipase C (PLC), which triggered two pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
145
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 43 publications
7
145
1
Order By: Relevance
“…6]. These observations are in agreement with previous reports identifying GABA as a chemoattractant (16).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6]. These observations are in agreement with previous reports identifying GABA as a chemoattractant (16).…”
Section: Resultssupporting
confidence: 92%
“…We developed a single-molecule assay in which the spatiotemporal dynamics of the distribution of individual GABA A Rs is monitored in response to a GABA gradient. The role of GABA as chemoattractant, like other neurotransmitters such as acetylcholine (Ach) and glutamate (8), has been previously documented (16). Our assay takes advantage of the brightness and photostability of quantum dots (QDs), which are used to fluorescently tag GABA A Rs and to track them at the single-nanoparticle level over long durations (tens of minutes), with good signal-to-noise ratio (Ϸ30) and with high localization accuracy (Ϸ10 nm) (17,18).…”
mentioning
confidence: 99%
“…Because guidance by a number of guidance cues has been shown to depend on both Rho family activity and local protein synthesis and degradation ( general events required for directional steering of growth cones in response to various guidance cues. Recent evidence suggests that GPCRs may have a role in axon guidance (Xiang et al, 2002). Our studies provide direct evidence that PACAP activation of its GPCR elicits attractive turning responses from growth cones.…”
Section: Discussionsupporting
confidence: 61%
“…These cells appear to include the population of young PSA-NCAM-positive granule neurons. Several previous studies have commented on the association of these PSA-NCAM-positive cells with neural progenitor cells and other young granule neurons in the SGZ/DG (Seki, 2002a(Seki, ,b, 2003.Given the chemoattractant role that SDF-1 plays for CXCR4-expressing progenitors during DG development (Bagri et al, 2002;Lu et al, 2002), and its additional role as an axonal guidance cue (Xiang et al, 2002;Arakawa et al, 2003;Chalasani et al, 2003;Pujol et al, 2005), it seems reasonable to suggest that release of SDF-1 from young granule neurons may be involved in guiding the migration and development of CXCR4-expressing progenitors and immature granule cells as they move from the SGZ into the granule cell layer proper.With respect to the SVZ and OB, we can similarly conclude that CXCR4 receptors are expressed by populations of neural progenitors in these areas. The localization of neural progenitors in the SVZ is also well established and, as in the DG, the pathway by which these cells subsequently develop has been defined in detail (Alvarez-Buylla and Lim, 2004;Merkle et al, 2004).…”
mentioning
confidence: 97%
“…Indeed, it is clear that the chemokine SDF-1 and its receptor CXCR4 play an important role in the development of the nervous system and other tissues. In the nervous system, SDF-1/CXCR4 signaling directs the migration of neural stem cells to a number of different parts of the brain (Zou et al, 1998;Bagri et al, 2002;Lu et al, 2002;Stumm et al, 2003) and the DRG (Belmadani et al, 2005) and also plays a role as an axonal guidance cue (Xiang et al, 2002;Arakawa et al, 2003;Chalasani et al, 2003;Lieberam et al, 2005;Pujol et al, 2005). It has also been demonstrated that neurospheres prepared from postnatal brains express CXCR4 as well as other chemokine receptors (Lazarini et al, 2000;Stumm et al, 2003;Ji et al, 2004;Peng et al, 2004;Tran et al, 2004) and that chemokines act as chemoattractants for these cells (Pluchino et al, 2005;Tran et al, 2004Tran et al, , 2005Widera et al, 2004), suggesting that chemokine-mediated effects may also be important in the regulation of adult progenitor cell migration.…”
mentioning
confidence: 99%